ÁGUAS PARA O DESERTO: O Processo de Adaptação Socioeconômica nos Reassentamentos da Usina Hidrelétrica de Salto Caxias - PR (1987-2017) - Marciniak, Fernando (2018)
This dissertation presents discussions about the problems that involved the process of construction of the Salto Caxias Hydroelectric Power Plant, an enterprise of Companhia Paranaense de Energia (COPEL), projected on the Iguaçu River. It started operating in 1999 with the challenge of expanding the supply of electricity that technically will possibility to accelerate the socioeconomic development of the State. The formation of this reservoir reached nine municipalities in the West and Southwest of Paraná, removing hundreds of families that had occupied the flooded territories for generations, through claims organized for social movements, those affected got the option of relocating in collective resettlement in the utopian perspective of prosperity emphasized by COPEL. The analyzes of this work are mainly focused on the transformations on the labor relations with the indemnified lands, which consequently implied in the modification of the economic, social and cultural principles of the affected ones, hindering drastically the processes of readaptations. This provide to the abandonment of activities in the field of small rural producers, as a result of the individual and collective difficulties of re-signifying their daily practices that remained against the mercadological interests of energy. In this sense, the contextualizations were based on oral sources collected through interviews provided for the characters that experienced this process of social modification, as well as the electrification projects of Paraná and the informative magazines elaborated by COPEL, presenting the propagandist ideologies of the energy sector that justified the needs of building Salto Caxias. Through this, it is possible to diagnose the multiple interests involved in these works, accompanied by historical developments.